Urbanization enhances consumer protist-driven ARGs dissemination in riverine ecosystems - Bob Adyari; Lanping Zhang; Ana Maravić; Jiaxin Chen; Laiyi Li; Mahmoud Gad; Chang-Ping Yu; Anyi Hu (Environment International)
Despite the emergence of antibiotic resistance genes (ARGs) and antibiotic resistant bacteria (ARBs), how biological inter-trophic interactions, modulated by watershed urbanization, shape the resistome remains unexplored. We collected water samples from the highly urbanized (western: 65 % built land, sewage-affected) and lesser-urbanized (northern: 25 % built land, drinking water source) downstream tributaries of the Jiulong River in southeast China over dry and wet seasons. We utilized metagenomic and amplicon (16S and 18S rDNA) sequencing to investigate the relationships among microeukaryotic algae, consumer protists, bacterial communities, and the resistome. Metagenomic results showed that ARG-MGE-carrying contigs (mobile ARGs), rather than ARG-carrying contigs (non-mobile ARGs), exhibited more pronounced discrepancies between tributaries. A higher total abundance of ARGs and a greater number of co-shared ARGs between pathogen and non-pathogen bacteria were observed in the more urbanized western tributary. Structural equation modeling revealed that consumer protist-bacteria and algae-bacteria cohesions predominantly influenced the resistome in the western and northern tributaries, respectively. Additionally, consumer protists had more significant associations (511 out of 634) with bacteria carrying mobile ARGs in western tributary, while algae had more significant associations (73 out of 105) in northern tributary. These results highlight the distinct inter-trophic driving factors of the resistome modulated by watershed urbanization.